Assessing human capital in the national wealth of Ukraine - Lutchyn, Nataliya (Ocena kapitału ludzkiego w bogactwie narodowym Ukrainy, 2021)
The study of the category of national wealth is necessary because the wealth of the nation is an important indicator of the economic power and potential of the country. However, today there are no equal views regarding the definition of the essence of national wealth. The aim of the article is to study the concept and structure of national wealth, the methods of its assessment, and most importantly – the ways to increase the national wealth of Ukraine. The main objective of this article is also to highlight the approaches of human capital measures and assessing its importance in the structure of national wealth. The article highlights the modern understanding of the essence and value of the category ‘national wealth’. The evolution of the methodological approaches to assessing national wealth and determining its components is considered. The need to include human capital to the national wealth has been confirmed and substantiated. Bettering human capital benefits individuals and their country and leads to improved sustainability for the future.
Śląski Przegląd Statystyczny = Silesian Statistical Review, 2021, Nr 19 (25), s. 41-52
Keywords: national wealth; human capital; produced capital; natural capital; analysis of variance; bogactwo narodowe; kapitał ludzki; wytwarzany kapitał; kapitał naturalny; analiza wariancji